DEFECTS IN THE VOICE OF PUPILS AND WAYS TO ELIMINATE IT - S. Askarova (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the defects found in the voice of schoolchildren and ways to eliminate them, the development of students ’ singing skills, and the work that must be carried out in order to properly educate the voice of students.